Uncertainty quantification and software risk analysis for digital twins in the nearly autonomous management and control systems: A review. (15th September 2021) - Lin, Linyu; Bao, Han; Dinh, Nam
Highlights: A two-tiered approach for digital twin development and assessment process. Uncertainty quantification is a key to digital twin bottom-up assessment. Software risk analysis is critical to digital twin top-down assessment. Techniques in uncertainty quantification and software risk analysis are reviewed. Abstract: A nearly autonomous management and control (NAMAC) system is designed to furnish recommendations to operators for achieving particular goals based on NAMAC's knowledge base. As a critical component in a NAMAC system, digital twins (DTs) are used to extract information from the knowledge base to support decision-making in reactor control and management during all modes of plant operations. With the advancement of artificial intelligence and data-driven methods, machine learning algorithms are used to build DTs of various functions in the NAMAC system. To evaluate the uncertainty of DTs and its impacts on the reactor digital instrumentation and control systems, uncertainty quantification (UQ) and software risk analysis is needed. As a comprehensive overview of prior research and a starting point for new investigations, this study selects and reviews relevant UQ techniques and software hazard and software risk analysis methods that may be suitable for DTs in the NAMAC system.